Can tablet video‐based telehealth assessment of the abdomen safely determine the need for abdominal imaging? A pilot study - Emily M. Hayden; Pierre Borczuk; Sayon Dutta; Michael R. Filbin; Shan W. Liu; Benjamin A. White; Eleonore Kugener; Blair A. Parry; Nora Horick; Kori S. Zachrison (Journal of the American College of Emergency Physicians Open)
Abstract Objective There is limited evidence on the reliability of video‐based physical examinations. We aimed to evaluate the safety of a remote physician‐directed abdominal examination using tablet‐based video. Methods This was a prospective observational pilot study of patients >19 years old presenting with abdominal pain to an academic emergency department July 9, 2021–December 21, 2021. In addition to usual care, patients had a tablet video‐based telehealth history and examination by an emergency physician who was otherwise not involved in the visit. Both telehealth and in‐person clinicians were asked about the patient's need for abdominal imaging (yes/no). Thirty‐day chart review searched for subsequent ED visits, hospitalizations, and procedures. Our primary outcome was agreement between telehealth and in‐person clinicians on imaging need. Our secondary outcome was potentially missed imaging by the telehealth physicians leading to morbidity or mortality. We used descriptive and bivariate analyses to examine characteristics associated with disagreement on imaging needs. Results Fifty‐six patients were enrolled; the median age was 43 years (interquartile range: 27–59), 31 (55%) were female. The telehealth and in‐person clinicians agreed on the need for imaging in 42 (75%) of the patients (95% confidence interval [CI]: 62%–86%), with moderate agreement with Cohen's kappa ((k = 0.41, 95% CI: 0.15–0.67). For study patients who had a procedure within 24 hours of ED arrival (n = 3, 5.4%, 95% CI: 1.1%–14.9%) or within 30 days (n = 7, 12.5%, 95% CI: 5.2%–24.1%), neither telehealth physicians nor in‐person clinicians missed timely imaging. Conclusion In this pilot study, telehealth physicians and in‐person clinicians agreed on the need for imaging for the majority of patients with abdominal pain. Importantly, telehealth physicians did not miss the identification of imaging needs for patients requiring urgent or emergent surgery.